2013
DOI: 10.1371/journal.pone.0062945
|View full text |Cite
|
Sign up to set email alerts
|

The Bacterial Pathogen Xylella fastidiosa Affects the Leaf Ionome of Plant Hosts during Infection

Abstract: Xylella fastidiosa is a plant pathogenic bacterium that lives inside the host xylem vessels, where it forms biofilm believed to be responsible for disrupting the passage of water and nutrients. Here, Nicotiana tabacum was infected with X. fastidiosa, and the spatial and temporal changes in the whole-leaf ionome (i.e. the mineral and trace element composition) were measured as the host plant transitioned from healthy to diseased physiological status. The elemental composition of leaves was used as an indicator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
50
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 50 publications
4
50
1
Order By: Relevance
“…fastidiosa, sandyi, morus, multiplex, and pauca. The disease mechanism, although not fully understood, involves formation of biofilm in the xylem vessels of host plants and obstruction of xylem sap transport leading to alteration of water and mineral nutrients in aerial plant parts (Chatterjee et al 2008;De La Fuente et al 2013). X. fastidiosa strains are vectortransmitted by xylem sap-feeding insects such as sharpshooters and spittlebugs (Redak et al 2004).…”
mentioning
confidence: 99%
“…fastidiosa, sandyi, morus, multiplex, and pauca. The disease mechanism, although not fully understood, involves formation of biofilm in the xylem vessels of host plants and obstruction of xylem sap transport leading to alteration of water and mineral nutrients in aerial plant parts (Chatterjee et al 2008;De La Fuente et al 2013). X. fastidiosa strains are vectortransmitted by xylem sap-feeding insects such as sharpshooters and spittlebugs (Redak et al 2004).…”
mentioning
confidence: 99%
“…Some authors have reported Zn deficiencies in X. fastidiosa-infected citrus leaves (11), whereas others have reported increased Zn levels in chlorotic areas of infected citrus leaves (9). Moreover, recent studies by our group show that infection with X. fastidiosa does not cause significant changes in the levels of Zn in hosts (7). Likewise, in vitro studies of the effect of Zn on X. fastidiosa have produced contradictory results: while supplementation of synthetic medium with Zn reduces the growth of X. fastidiosa (12,13), Zn concentrations in xylem vessels have been positively (14) or negatively (15,16) correlated with growth of X. fastidiosa.…”
mentioning
confidence: 77%
“…Two hundred microliters of the suspension was used directly for DNA extraction (three replicates) using a modified cetyltrimethylammonium bromide (CTAB) protocol (29), 200 l was treated with ethidium moanoazide (EMA) (30) and subsequently used for DNA extraction (three replicates), and 100 l of the appropriate suspension dilution was plated on PW agar plates (two replicates), prior to a repeated homogenization step, and incubated at 28°C for 2 weeks for enumeration of CFU. For the planktonic phase, a 1.5-ml aliquot was collected and treated in the same manner as the biofilm at each time point (3,5,7, and 10 days p.i.). Three biological replicates were used per treatment, and two independent experiments were performed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations